Growth parameters and density variation of a queen conch, Strombus gigas (Neotaenioglossa: Strombidae), population from Xel-Ha park, a marine protected area - Baqueiro Cárdenas, Erick (2014)
The queen conch, Strombus gigas, is a gastropod of commercial importance in the Caribbean. Population studies are based on size frequency analysis, using either length or weight parameters for the whole live organism. This contribution used mark-recapture data to estimate the Von Bertalanffy equation parameters and population number variation within a non harvest population from a protected area, to clarify the biometric parameters that better suit for the whole population, or for the juvenile and adult fractions. Conchs from Xel-Ha Park were monthly sampled from November 2001 to August 2005. Every conch found was measured and marked with a numbered tag that identified month and locality; and monthly abundance was estimated with Jolly’s method. Length, lip thickness and weight increments were used to estimate the Von Bertalanffy growth equation parameters with Appeldoorn’s subroutine of FISAT program. The population number varied through the study, with a minimum of 49 in April 2003 and maximum of 9 848 during June 2005. Conchs make only temporary use of Xel-Ha cove. Shell length gave the best fit for the juvenile fraction: L∞=251, K=0.3, C=0.8 Wp=0.3; and lip thickness for adults: L∞=47.78, K=0.17, C=0.1, Wp=0.86, while, the whole population was better represented by weight: L∞=3850, K=0.36, C=0.8, Wp=0.3. A maximum age of 19 years was estimated from the population. Natural mortality was 0.49/year for juveniles and 0.29/year for adults. There were two pulses of recruitment: fall-winter and summer. It is concluded that population studies from length frequency data, should be analyzed independently in two groups, shell for the juvenile fraction and lip thickness for the adult fraction, or if it is not possible to analyze the population fractions separately, weight should be used to avoid miss calculation of the age structure.